2007
DOI: 10.1523/jneurosci.3039-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness in Congenital Amusia: When Less Is Better Than More

Abstract: Congenital amusia (or tone deafness) is a lifelong disorder characterized by impairments in the perception and production of music. A previous voxel-based morphometry (VBM) study revealed that amusic individuals had reduced white matter in the right inferior frontal gyrus (IFG) relative to musically intact controls (Hyde et al., 2006). However, this VBM study also revealed associated increases in gray matter in the same right IFG region of amusics. The objective of the present study was to better understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
191
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(222 citation statements)
references
References 31 publications
27
191
1
3
Order By: Relevance
“…Structural neuroimaging data reveal subtle differences in the brains of individuals with congenital amusia in the inferior frontal cortex and superior temporal areas, variously in the left hemisphere (20,21) or the right (22). The finding of morphological differences outside the temporal cortex is congruent with findings from functional imaging studies showing activation of frontal and temporal areas when pitch information must be integrated or compared over time (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Structural neuroimaging data reveal subtle differences in the brains of individuals with congenital amusia in the inferior frontal cortex and superior temporal areas, variously in the left hemisphere (20,21) or the right (22). The finding of morphological differences outside the temporal cortex is congruent with findings from functional imaging studies showing activation of frontal and temporal areas when pitch information must be integrated or compared over time (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…In a subsequent study abnormal cortical thickness was demonstrated in the right superior temporal lobe and the right frontal operculum (Fig 1). 17 …”
Section: Basis For the Phenotype 2: Direct Evidence For A Cortical DImentioning
confidence: 99%
“…Congenital amusia is a neurogenetic disorder that is characterized by a deficit in melody processing that cannot be explained by hearing loss or intellectual deficiencies (30). Congenital amusia is hereditary (31,32) and is associated with reduced connectivity between the right auditory and inferior frontal cortices (33)(34)(35). The root functional cause of the musical impairments appears to lie in the processing of pitch.…”
mentioning
confidence: 99%